Sastra Sebagai Representasi Problematika Kebebasan Ruang Publik: Kajian Novel Al-Karnak Karya Najib Mahfuz / Literature As A Representation Of The Problems Of Freedom In Public Space: A Study Of Najib Mahfuz's Novel Al-Karnak - Amiroh Nichayatun Munir Azizah; Sukron Kamil (Diwan : Jurnal Bahasa dan Sastra Arab, 2022)
هذه المقالة تهدف إلى الكشف عن كيفية تصوير استغلال حرية الفضاء العام في رواية الكرنك. تشمل هذه المقالة أنواع البحوث النوعية الوصفية. ثم استخدم الباحثون منهج حرية المجتمع مع تحليل النص. استخدم الباحثون مصادر البيانات الأولية برواية الكرنك لنجيب محفوظ. وفي الوقت نفسه فإن المصادر الثانوية في هذا البحث هي العناصر الداخلية في الأعمال الأدبية والكتب، والمقالات، والمجلات، والإنترنت ومعلومات البيانات التي لا تزال ذات صلة بموضوع المقالة. نتيجة هذه المقالة أن هناك المشاكل حول حرية الفضاء العام في خضم السياسات القمعية التي تشمل: (1) حدود المرأة في التعبير عن الرأي، (2) إسكات المواطنين الذين اختلفوا مع الحكومة، (3) الأزمة عن ثقة الجمهور في الحكومة. إن وجود رواية الكرنك في هذا المجال معناه يمثل انتقاداً لرئيس جمال عبد النصر. فإن نجيب محفوظ قد انتقد جمال عبد النصر الذي ليس له امكانية على تحقيق الديمقراطية والحرية للشعب وفقًا لوعوده السياسية في بناء العدالة الاجتماعية من خلال حرية الدينية، وحرية الصحافة وحرية الإجتماعية. مع أن هذه الرواية أيضًا أظهرت انكسار حدود المجتمع أمام سيطرة الحكومية، على الرغم من التزام حكومة جمال عبد النصر في مجال الديمقراطية. الكلمات المفتاحية: الحرية؛ منطقة العامة؛ الكرنك؛ نجيب محفوظ. Abstract The purpose of this research is to paint a picture of the novel al-exploitation Karnak's of public sphere freedom.. This study uses qualitative methods that produce descriptive data. Then the researcher used the freedom of the public sphere approach by analyzing the text. The primary source used by the researcher is the novel al-Karnak by Najib Mahfuz. Meanwhile, secondary sources in this research are intrinsic elements in literary works, books, papers, journals, the internet, or information and data that are related and still relevant to the object of study. This research shows that there are problems with the freedom of the public sphere, including: (1) the limitations of women in expressing opinions; (2) the silencing of citizens who disagree with the government; and (3) a crisis of public trust in the government. The presence of the novel al-Karnak implicitly represents a criticism of the president of Jamal 'Abd al-Nasir. Najib Mahfuz criticized Nasir as a president who was unable to realize democracy and freedom for the people according to his political promises of building social justice through guarantees of freedom of religion, freedom of the press, association, and opinion. This novel also does not describe the slightest bit of control from the people, even though Nasir's administration has adhered to the principle of democracy.